Probation and the ethics of care - Dominey, Jane (Probation journal, 2022)
Discussions of probation's values can be enriched by an appreciation of care ethics. This approach is explained with attention to its emphasis on relationships and individualisation. The implications for probation's work are explored, including its significance for the supervisory relationship, its challenges for the management of the organisation and the value of individualised approaches. Care ethics argues for practice shaped not by rules and processes, but by people and their circumstances in all their diversity. Care ethics offers a principled and effective approach to probation's work.